Serum creatinine-to-cystatin C ratio and 1-year mortality risk in advanced breast cancer patients: a multicenter retrospective cohort study - Deng, Huijie; Yang, Jiacheng; Zheng, Guanyu; Zhang, Biyao; Wang, Yuzhou; Wu, Yuye; Mo, Shufen; Huang, Shengchao; Zhang, Yuanqi; Li, Lixia (Frontiers in Nutrition, 2025)
BackgroundMuscle wasting and sarcopenia in advanced breast cancer correlates with poor outcomes. The serum creatinine-to-cystatin C ratio (CCR) is a potential muscle mass biomarker, but its prognostic value in advanced breast cancer is unclear.MethodsThis multicenter retrospective cohort study included 465 patients with stage III-IV breast cancer (2018–2023) receiving standard treatment. The creatinine-cystatin C ratio (CCR) was calculated based on baseline serum markers. The primary endpoint was the 1-year all-cause mortality rate, as assessed through medical records and follow-up. A multivariate Cox regression model was used to analyze the relationship between CCR and mortality, along with restricted cubic spline, Kaplan–Meier survival analysis, ROC curve, and subgroup analysis.ResultsThis study enrolled a total of 465 patients with stage III-IV breast cancer, with a median age of 52.0 (interquartile range [IQR], 47.0–60.0)years and a median creatinine-cystatin C ratio (CCR) of 1.0 (IQR, 0.8–1.2). The 1-year mortality rate among all patients was 26.2% (122/465), with a mortality rate of 18.1% (52/288) for stage III patients and 39.5% (70/177) for stage IV patients. Multivariate Cox proportional hazards regression analysis showed a significant negative association between CCR and 1-year all-cause mortality in breast cancer patients (adjusted HR = 0.68, 95% CI: 0.63–0.74, p < 0.001). Compared with the lowest quartile group (Q1), the highest quartile group (Q4) had a mortality risk reduction of 94% (HR = 0.06, 95% CI: 0.03–0.14, p < 0.001). Restricted cubic spline analysis confirmed a linear negative association between the two (P for non-linear = 0.178). The Kaplan–Meier survival curves showed a significantly higher 1-year all-cause mortality in the Q1 group (p < 0.0001). The area under the curve (AUC) for predicting 1-year mortality was 0.802 (95% CI: 0.756–0.849). Subgroup analysis revealed a significant interaction between CCR and chemotherapy (p = 0.013) and clinical stage (p < 0.001), while the negative correlation persisted in other subgroups. Sensitivity analysis using unadjusted data yielded consistent results (Q4 HR = 0.06, 95% CI: 0.02–0.14), confirming the robustness of the study conclusions.ConclusionThe serum creatinine-cystatin C ratio is an independent predictor of 1-year mortality risk in advanced breast cancer, with higher levels associated with significantly reduced mortality.